An efficient way to convert 1D signal to 2D digital image using energy values - Azad, Muntasir; Khaled, Faiyaz; Rumman, Md. Rakib Hasan (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.